Updated review on contaminant communication experiences in the circumpolar Arctic - Eva M. Krümmel; Amanda D. Boyd; Danielle Brandow; Michael Brubaker; Chris M. Furgal; Robert Gerlach; Brian D. Laird; Mélanie Lemire; Lisa L. Loseto; Gert Mulvad; Shannon P. O’Hara; Kristin Olafsdottir; et al. (International Journal of Circumpolar Health)
Arctic populations are amongst the highest exposed populations to long-range transported contaminants globally, with the main exposure pathway being through the diet. Dietary advice is an important immediate means to address potential exposure and help minimize adverse health effects. The objective of this work is to enable easier access to dietary advice and communication guidance on contaminants with a focus on the Arctic. This manuscript is part of a special issue summarizing the Arctic Monitoring and Assessment Programme’s Assessment 2021: Human Health in the Arctic. The information was derived with internet searches, and by contacting relevant experts directly. Results include risk communication efforts in European Arctic countries, effectiveness evaluation studies for several Arctic countries, experience of social media use, and the advantages and challenges of using social media in risk communication. We found that current risk communication activities in most Arctic countries emphasize the importance of a nutritious diet. Contaminant-related restrictions are mostly based on mercury; a limited amount of dietary advice is based on other contaminants. While more information on effectiveness evaluation was available, specific information, particularly from Arctic countries other than Canada, is still very limited.